2020
DOI: 10.17269/s41997-020-00390-7
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy among parents of preschoolers in Canada: a systematic literature review

Abstract: Objectives The purpose was to synthesize the available literature on what factors influence vaccine hesitancy of parents of preschoolers in Canada. Methods Databases (e.g., CINAHL, PubMed, OVID, Proquest) were searched for relevant research articles produced between January 2009 and October 2019. Articles were required to examine vaccine uptake in children aged 0-7, in the English language, and focused within a Canadian context. Articles were excluded if they focused on uptake of the influenza vaccine and if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
(254 reference statements)
0
23
0
Order By: Relevance
“…Regarding children's vaccination, the role of parents is crucial as they decide whether to vaccinate their children. In a recent systematic review, only 50-70% of Canadian 2-year-old children have received all of the recommended vaccines (Schellenberg and Crizzle, 2020). Parental vaccination decisions are complex and a variety of factors influence parents' decision to vaccinate or not their children such as trust in access to healthcare providers, health perceptions and practices, healthcare system, attitudes toward vaccines, experiences, risks and effects of vaccination, religious issues, trust in science, information sources, emotions, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding children's vaccination, the role of parents is crucial as they decide whether to vaccinate their children. In a recent systematic review, only 50-70% of Canadian 2-year-old children have received all of the recommended vaccines (Schellenberg and Crizzle, 2020). Parental vaccination decisions are complex and a variety of factors influence parents' decision to vaccinate or not their children such as trust in access to healthcare providers, health perceptions and practices, healthcare system, attitudes toward vaccines, experiences, risks and effects of vaccination, religious issues, trust in science, information sources, emotions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Parental vaccination decisions are complex and a variety of factors influence parents’ decision to vaccinate or not their children such as trust in access to healthcare providers, health perceptions and practices, healthcare system, attitudes toward vaccines, experiences, risks and effects of vaccination, religious issues, trust in science, information sources, emotions, etc. (Caso et al, 2021; Dubé et al, 2018; Nurmi and Harman, 2021; Schellenberg and Crizzle, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, there has been an increase in the development of strategies aiming to promote vaccine uptake in children and youth. We highlight four key strategies below; however, there are also necessary but insufficient conditions that are pivotal to all of the following strategies such as the availability of free vaccination, 21 the promotion of trust in vaccines and health services, 22 tailoring clear messaging regarding risks and benefits to developmental ages, and surveillance systems to monitor vaccine safety and uptake. 23 It is also important for any strategy to acknowledge and prepare for scenarios in which youth want to get vaccinated, but parents do not (or vice versa).…”
Section: Evidence-based Strategies To Increase Vaccine Uptake In Children and Youthmentioning
confidence: 99%
“…Healthcare provider recommendation is a well-researched strategy for increasing vaccine uptake in children. 22,[26][27][28][29] In order for healthcare providers to make an effective vaccine recommendation, it is necessary to inform, prompt and provide educational training and resources to providers about evolving COVID-19 vaccine recommendations and the rationale for vaccinating children and youth. 16,[30][31][32][33][34][35][36][37][38][39] It may be helpful to partner with primary care providers to administer vaccines in their offices, 40 and ensure parents are supported to have adequate paid time off for their children's appointments.…”
Section: Healthcare Provider Recommendationmentioning
confidence: 99%
“…4,5 The United States is still far from achieving herd immunity, with about 54% of Delawareans being fully vaccinated and uptake for COVID-19 vaccines declining. [6][7][8] Several studies in adults have demonstrated that Black adults, adults from rural areas, and adults from households with lower incomes have higher rates of COVID-19 vaccine hesitancy 6,[9][10][11][12][13] exacerbated by systemic issues of institutional racism, distrust of the healthcare system, misinformation, and complacency with the pandemic. 14,15 However, there have been only a handful of studies assessing caregiver hesitancy towards a COVID-19 vaccine for their children, 6,[16][17][18][19][20] with the most recent national survey showing that less than half of caregivers in the United States were likely to vaccinate their children against COVID-19 and increased hesitancy among parents of younger children those with lower educational status and non-Democratic affiliations.…”
Section: Introductionmentioning
confidence: 99%